2016
DOI: 10.4236/cm.2016.71004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cupping Therapy on Skin’s Biomechanical Properties in Wistar Rats

Abstract: Cupping therapy has been widely used for clinical treatment of soft tissue lesions. The current study investigated the effects of cupping therapy on biomechanical properties of the skin in Wistar rats. 20 rats were divided into two groups: 10 in experimental and 10 in control group. Either the right or the left lower quadrants of the lumbar regions in the experimental group underwent 10 minutes daily cupping therapy for 12 days. The skin stiffness and ultimate tensile strength of all the rats were measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In this study, we selected a middle value of 300 mm Hg. Several studies suggested that the duration of cupping therapy should range from 5 to 20 minutes 28,29 . We selected cupping therapy for 5 minutes in this study because the upper arm has rich blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we selected a middle value of 300 mm Hg. Several studies suggested that the duration of cupping therapy should range from 5 to 20 minutes 28,29 . We selected cupping therapy for 5 minutes in this study because the upper arm has rich blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we chose -300 mmHg for cupping therapy because a negative pressure between -225 and -375 mmHg is commonly applied to treat musculoskeletal impairments (Al-Bedah et al, 2016). We chose 5 min for the duration of cupping therapy because previous studies have used durations ranging from 5 to 20 min for different impairments (Sanders et al, 1995;Tham et al, 2006;Dayer-Berenson, 2010;Roostayi et al, 2016). Our previous studies demonstrated that cupping therapy at -300 mmHg for 5 min could significantly increase skin blood flow of the upper arm (Hou et al, 2020).…”
Section: Cupping Therapy Dosementioning
confidence: 99%
“…Cupping can impose a tensile stress on the subcutaneous tissues, which results in the surface tissues and deeper layers being drawn into the cup (Tham, Lee, & Lu, ). This biomechanical effect can result in local stretching, releasing the myofascial and scar tissue, and decreasing skin stiffness and the ultimate tensile strength (Roostayi, Norouzali, Dehghan Manshadi, & Akbarzadeh Baghban, ). In addition, cupping can lead to pain reduction and improved blood flow and oxygenation (Bhikha et al, ; Chirali, ; Li, Liting, Xiaolin, et al, ).…”
Section: Introductionmentioning
confidence: 99%